2009
DOI: 10.1177/0883073808327836
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Tonic Upgaze Presenting as a Clinical Isolated Syndrome

Abstract: We report a 3.5-year-old boy with sudden onset of episodic upward deviation of the eyes that led to diagnosis of paroxysmal tonic upgaze. Cranial magnetic resonance imaging showed right-hand side dominant bilateral hyperintense lesions in the mesencephalon and the thalamus on T2-weighted images. These lesions suggested a demyelinating pathology. Corticosteroid treatment was started. The episodes of upward eye deviation and the lesions on magnetic resonance imaging completely resolved after 3 days and 3 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The reported results of imaging studies for most children with PTU have been normal, with the exception of some cases with hypomyelination or delayed myelination, or with lesions within the oculomotor pathway, 12,13 which is mostly located within the midbrain and brainstem.…”
Section: Discussionmentioning
confidence: 98%
“…The reported results of imaging studies for most children with PTU have been normal, with the exception of some cases with hypomyelination or delayed myelination, or with lesions within the oculomotor pathway, 12,13 which is mostly located within the midbrain and brainstem.…”
Section: Discussionmentioning
confidence: 98%
“…Since none showed pathological brainstem changes, brainstem injury was not considered to be the cause of the disease (4). A few studies have reported abnormal brain MRI results in PTU patients, showing hypomyelination, delayed myelination, or lesions within bilateral mesencephalon and thalamus on brain MRI (17,18). Nevertheless, the majority of affected children have normal MRI performance.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is usually classified as a benign transient movement disorder in children (Ouvrier and Billson, 2005). Nevertheless, paroxysmal gaze deviation may also be an early sign of more widespread neurological dysfunction and has been reported in association with specific inflammatory or compressive lesions involving the periaqueductal grey structure (Spalice et al , 2000; Senbil et al , 2009). Due to a lack of specific clinical features, we were unable to classify the paroxysmal gaze manifestation presented by our patient as paroxysmal tonic upgaze per se.…”
Section: Discussionmentioning
confidence: 99%